2021
DOI: 10.1080/1177083x.2020.1865418
|View full text |Cite|
|
Sign up to set email alerts
|

Attitudes to noise and behaviour towards hearing protection among Pasifika university students in New Zealand

Abstract: It is estimated that 1.1 billion young people worldwide are at risk of hearing loss due to high levels of noise exposure. Hearing loss can contribute to low self-esteem, poor employment prospects and social problems. The aim of this research was to explore the attitudes and beliefs towards noise, hearing loss and hearing protection among Pasifika university students in New Zealand. 96 Pasifika students completed the Youth Attitude to Noise Scale (YANS) and Beliefs About Hearing Protection and Hearing Loss (BAH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
3
2
Order By: Relevance
“…The YANS score in our study was slightly lower than those reported from Brazilian young adults[ 33 ] and New Zealand students[ 34 ], but higher than the mean entire YANS score in Belgium. [ 18 ] In our study, females had more difficulties concentrating in noisy environments compared to males, which is consistent with other studies.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…The YANS score in our study was slightly lower than those reported from Brazilian young adults[ 33 ] and New Zealand students[ 34 ], but higher than the mean entire YANS score in Belgium. [ 18 ] In our study, females had more difficulties concentrating in noisy environments compared to males, which is consistent with other studies.…”
Section: Discussioncontrasting
confidence: 93%
“…[ 35 ] Concerning the attitudes toward daily noises, earlier studies showed more negative attitudes of boys compared to girls. [ 33 ] However, this finding was not confirmed in our study. We show that students who find it difficult to concentrate in noisy environments are more prone to depression.…”
Section: Discussioncontrasting
confidence: 89%
“…The stigmatization in the Hispanic community could be explained by the negative colloquial connotation of sordo (deaf) for HL (Marrone et al, 2017). In a study conducted at Pasifika University in New Zealand, students' knowledge of HL was measured (Reddy et al, 2021), and researchers found that most of the students had great knowledge and awareness of the risks and consequences of HL but held poor attitudes when discussing measures to minimize noise exposure in their daily environment, such as discos, dances, concerts, and sporting events (Reddy et al, 2021). Similar responses have been reported among Hispanic construction workers, who refer that use of hearing protective devices was seen as a hassle or useless since they believed HL would not happen to them (Robertson et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This questionnaire has previously been used and validated in South Africa (Keppler et al, 2015 ) and internationally such as in New Zealand (Reddya et al, 2021 ), Colorado (Hickey, 2019 ) and Sweden (Svensson et al, 2004 ). In addition to the questionnaire’s internal consistency being previously investigated by Gilles et al ( 2013 ) and Keppler ( 2010 ), the results of a research investigation into the test-retest reliability of the BHPHL questionnaire revealed that there was no noteworthy association between the test and retest, and the variances in the scores of the BAHPHL questionnaire (as determined by Pearson correlation, p > 0.05) (Sofie et al, 2018 ).…”
Section: Research Methods and Designmentioning
confidence: 99%